2011
DOI: 10.1111/j.1525-1594.2010.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Genetic Algorithm for Multiobjective Design Optimization of the Femoral Stem of a Cemented Total Hip Arthroplasty

Abstract: There are many designs of the femoral stem of a cemented total hip arthroplasty, and mechanical failure of the stem is caused by several factors related to the cement, such as failure of the cement. Optimization of the shape of the stem, especially multiobjective optimization, is required to solve these design problems because a cement fracture is caused by multiple factors. The objective of this study was to determine a stem geometry considering multiple factors at the same time. A three-dimensional finite el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It was also revealed that shorter stems had improved the overall stability of the cemented fixation and provided the femur with more proximal load [25]. Implant shape modification techniques were also investigated in cemented and cementless fixations; common design optimizations in the former fixation targeted the cement layer or cement-prosthesis interface with the objective of minimizing stress concentration in these areas [2628]; however stress shielding of the bone was not quantified for use in the design analysis. Several shape optimization models were developed for cementless prostheses where one [27, 2932] or more [3335] performance criteria were used in the search method.…”
Section: Introductionmentioning
confidence: 99%
“…It was also revealed that shorter stems had improved the overall stability of the cemented fixation and provided the femur with more proximal load [25]. Implant shape modification techniques were also investigated in cemented and cementless fixations; common design optimizations in the former fixation targeted the cement layer or cement-prosthesis interface with the objective of minimizing stress concentration in these areas [2628]; however stress shielding of the bone was not quantified for use in the design analysis. Several shape optimization models were developed for cementless prostheses where one [27, 2932] or more [3335] performance criteria were used in the search method.…”
Section: Introductionmentioning
confidence: 99%
“…Several optimization techniques in the orthopaedic biomechanics field have been widely used to obtain the optimal shape according to specific requirements (Huiskes and Boeklagen 1989;Kuiper and Huiskes 1997;Kowalczyk 2001;Fernandes, Folgado, and Ruben 2004;Sabatini and *Corresponding author. Email: dkpra@mech.iitkgp.ernet.in Goswami 2008;Fraldi et al 2010;Boyel and Kim 2011;Ishida et al 2011;Ruben, Fernandes, and Folgado 2012). Most of these techniques are related to shape optimization of the femoral component.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of total hip replacement, several optimization procedures have been used to determine the optimal design of the femoral stem (Huiskes and Boeklagen 1989;Kuiper and Huiskes 1997;Kowalczyk 2001;Fernandes, Folgado, and Ruben 2004;Ruben, Fernandes, and Folgado 2012;Sabatini and Goswami 2008;Fraldi et al 2010;Ishida et al 2011;Boyel and Kim 2011). Studies by Kuiper and Huiskes (1997) and Nobari et al (2010) considered minimization of bone density loss (bone resorption) as an objective function for the optimal design of the femoral stem and plate.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, reduced micromotion and improved long-term stability were observed in fully cemented fixations [19, 20] and with shorter stem lengths [21]. Alternatively, modifying the implant shape by minimizing the stress concentration on the cement interface or within the cement mantle near the proximal or distal ends of the implant was also considered in a number of studies [2224] where, despite the diversity of objective functions and numerical schemes employed in these investigations, stress shielding was not part of the design objectives.…”
Section: Introductionmentioning
confidence: 99%